Guidelines for thermal management design of hydride containers - Melnichuk, Maximiliano (2012)
Hydrogen storage by means of hydride forming alloys has been intensely studied during last three decades. Container heat management is among the most relevant aspects of study in this field, particularly because in many cases it is the limiting factor for charge and discharge rate. However, given the complexity of the container system and the great variety of possible configurations (type of absorbing material, geometry of the container, hydrogen charge pressure, cooling temperature, etc.), according to the authors´ best knowledge, yet there is no general rule for hydride containers design. In this paper we propose general design guidelines using non-dimensional parameters to assess the thermodynamic and kinetics behavior in order to predict the absorption fill up time.